2013
DOI: 10.1097/cji.0b013e3182948452
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced Killer Cells in Combination With Transcatheter Arterial Chemoembolization and Radiofrequency Ablation for Hepatocellular Carcinoma Patients

Abstract: This study evaluated the clinical efficacy of autologous cytokine-induced killer (CIK) cell transfusion in combination with transcatheter arterial chemoembolization (TACE) and radiofrequency ablation (RFA), compared to sequential therapy with TACE and RFA, for the treatment of hepatocellular carcinoma (HCC). We retrospectively studied 2 groups of HCC patients: 85 patients in the TACE+RFA+CIK group were treated with adoptive autologous CIK cell transfusion in combination with minimally invasive therapy, 89 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 0 publications
1
64
1
Order By: Relevance
“…Of these, 1 patient with lymphoma experienced complete remission, while 6 patients exhibited disease progression, and 3 did not experience any alteration on their condition (5,11). Other clinical studies subsequently confirmed the safety and benefits of CIK cell-based therapy, alongside initial clinical activity (12,13).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Of these, 1 patient with lymphoma experienced complete remission, while 6 patients exhibited disease progression, and 3 did not experience any alteration on their condition (5,11). Other clinical studies subsequently confirmed the safety and benefits of CIK cell-based therapy, alongside initial clinical activity (12,13).…”
Section: Introductionmentioning
confidence: 68%
“…Furthermore, CIK cells are able to regulate cellular immune functions in patients with cancer (35,36). The application of CIK cells as adoptive immunotherapy is important in the treatment of cancer, since several clinical studies have confirmed the safety of CIK therapy for patients (12,13). Numerous clinical studies have been recently performed, whereby adjuvant infusions of CIK cells following surgical resection demonstrated a significant increase in survival time (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2013) showed that the disease control rate was 67.7% in patients transfused with CIK cells (Wang et al, 2013). Similarly, in HCC patients, Huang et al (2013) showed that CIK cell immunotherapy was valuable therapeutic strategy to prevent recurrence and metastasis in HCC patients after TACE and RFA (Huang et al, 2013). Effects of CIK cell transfusion caused a significant increased of CD3+, CD4+, CD4+CD8+ and CD3+CD4+ T cells , improved the immunological status in HCC patients (Shi et al, 2004), reduce the level of serum AFP and anti-HBV and decrease the 1-year recurrence rate of patients with HCC after curative TACE plus RFA (Pan et al, 2010).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Recently, escalating proof from clinical trials demonstrated that CIK cells adoptive transfer demonstrated a substantial anti-tumor effect in patients with solid tumors and hematological malignancies [92][93][94] . Some reports showed that CIK adjuvant immunotherapy significantly improved the outcomes of HCC patients [95][96][97][98][99][100][101] . In these studies, CIK cell transfusion reduced the relapse rate of HCC in patients after TACE and RFA therapy and prolonged the disease-free survival and OS for HCC patients after radical resection or TACE.…”
Section: Cytokine-induced Killer Cellsmentioning
confidence: 99%